Organisasi Paranoid: Ancaman Disintegrasi Sosial-Manajemen - Danial Kusumah (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2022)
This study aims to examine the sources, impacts, and ways to overcome paranoid organizations by using a qualitative approach in the method of analysis and reviewing the literature on the research design. Through the elaboration process carried out in the context of the study, the results of the study reveal that there are 5 (five) types of pathological organizations, namely dramatic organizations, suspicious organizations, compulsive organizations, detached organizations, and depressive organizations. The main sources of paranoid organizations are restructuring, leadership styles, and identity politics. If not taken seriously, the paranoid organizational conditions will lead to widespread and deep-rooted conflicts and have implications for social-management disintegration. This will contribute to management dysfunction and hinder the achievement of organizational goals. Massive, structured, and systematic efforts are needed to prevent and overcome the negative consequences of paranoid organizational conditions. This study recommends several variables that must be considered and implemented by management, namely conflict management, internalization of social values, and the application of the right leadership style.